Musculoskeletal symptoms and training characteristics differ between sex and playing positions: A cross-sectional study among high-performance Brazilian beach handball players - de Carvalho-Nicolau, R.; Bittar, S. T.; Tilp, M.; de Azevedo Lago, S.; dos Santos Oliveira, L. (International Journal of Sports Science & Coaching, 2023)
This study analysed self-reported musculoskeletal symptoms and training characteristics of high-performance Brazilian beach handball athletes. In a cross-sectional study, 28 men (mean (standard deviation), age: 23 (5) years, body mass: 81.9 (14.4) kg, height: 181.3 (8.6) cm, experience: 13.3 (5.4) years) and 27 women (mean (standard deviation), age: 28 (8) years, body mass: 65.5 (12.7) kg, height: 170.4 (4.9) cm, experience: 9.3 (3.0) years) answered an online questionnaire about anthropometric and sociodemographic aspects, musculoskeletal symptoms, and training characteristics. The results showed that the musculoskeletal symptoms are more prevalent in the knees during the previous seven days and in the shoulder during the previous 12 months. Left-wing players were more affected by musculoskeletal symptoms in the shoulder than right-wing players and central defenders during the previous seven days regardless of the sex. Problems in the elbow area presented a higher prevalence in the male players compared to the female players in the past 12-month period. The training volume was higher for men compared to women, regardless of the playing position. Moreover, beach handball athletes who reported training five days/week or 360 min/week or more were more likely to develop musculoskeletal symptoms in the elbow compared to those who had a lower frequency and duration of training. Musculoskeletal symptoms occurred most in the shoulders and knees, differing between sex and playing positions. Higher frequency and duration of training were independent risk factors for chronic musculoskeletal symptoms in the elbow compared to a lower volume of training.